在地取向、課程與原住民：教育人類學的觀點 The Inculturation Approach, Curriculum, and Indigenous Peoples: From the Aspect of Anthropology of Education - 黃約伯 Yueh-Po Huang; 劉秋玲 Chiu-Ling Liu; 丁進添 Chin-Tien Ding (Higher Education Foundation, 2017)
本研究從教育人類學的觀點探討在地取向與原住民高等教育的關係，首先說明 原住民高等教育興起的背景，並說明現行全球原住民高等教育發展的趨勢與國外施 行在地取向的原住民高等教育。基本上，原住民高等教育於二十世紀漸漸興起，此 一發展係由於西方高等教育制度背負同化與殖民的歷史，也是由於前者長期未能認 肯原住民傳統知識與科學將其納入校園課程當中。其次，本研究則透過田野研究， 具體說明臺灣一所大學與鄰近泰雅族部落進行在地取向的課程實例，據此說明大學 與原住民部落建立夥伴關係的過程與相關議題。最後，對於大學在地取向田野實例 進行反思並提供後續研究的方向。 This article aims to explore the application of the inculturation approach in indigenous higher education. It first looks at the emergence and development of indigenous higher education in the contemporary world. It then reviews theoretical approaches to indigenous higher education, including countries such as USA, New Zealand, Japan, and Taiwan, which currently applying inculturation approaches to their respective universities. A literature and theoretical review will be followed by a 'singlesited' ethnography: The Inculturation of one Atayal community in Wulai, New Taipei City, into one national university in Taiwan. The ethnographical account reveals the innovative educational and social practices employed by that university which played a prominent part in the establishment and maintenance of good relationships with that Atayal community. It also uncovers certain practices that appeal to local Atayal people, including the establishment of a community office, the empowerment of the Atayal people and the coordination of a social network (local district office, schools, churches, civic organizations and so forth). Based on these specific ethnographical findings, the authors reflect on the inculturation approach more generally and make further concluding remarks to this research.